Case Series: Confirmed Diphtheria at Sulianti Saroso Infection Center Hospital in The Post-pandemic Period - Nugroho, Anita Puspitasari Dyah; Herlina, Herlina; Hendrawati, Nunung; Aliza, Nur; Hartono, Teguh Sarry; Widiantari, Aninda Dinar; Murtiani, Farida (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Diphtheria vaccine coverage decreased during the Covid-19 pandemic. Diphtheria is caused by Corynebacterium diphtheria, which infects the upper respiratory system and produces toxins circulating in the body. The disease was fatal, with a mortality rate higher in children. This study described a case series of confirmed hospitalised diphtheria patients at Sulianti Saroso Infectious Disease Hospital (SSIDH) eighteen months post-pandemic. Objective: to describe epidemiological characteristics, laboratory examinations and outcomes of hospitalised diphtheria patients at SSIDH from January 1st, 2022, to June 31st,2023. Case Presentation: We reported ten confirmed diphtheria cases based on RT-PCR and clinical and epidemiological diagnosis. Of the ten cases, nine were children (<18 years old), six were male patients, and five lived in Jakarta. Based on Albert staining, 9 of 10 samples were found to be bacilli, positive-gram bacteria with metachromatic granular. Result: According to the RT-PCR examination, eight cases were confirmed positive for toxigenic diphtheria, five were a mitis subtype, one was a gravis subtype, and the other four were undetected. Based on clinical examination, eight cases were classified as severe diphtheria, five cases included myocarditis, and three patients passed away. Pediatric cases dominated diphtheria cases. RT-PCR examinations are more accurate and specific to finding toxigenic subtypes in the Jakarta Metropolitan Area. Conclusion: The detection of diphtheria cases in adult’s highlights concerns about adult immunity and awareness of vaccination. Vaccination campaigns and booster shots are essential, alongside continuous surveillance and accurate testing to prevent a resurgence of the disease.